Development of a technology for coal conversion in the presence of coal tar - Baikenov, M.I.; Omarbekov, T.B.; Fengyun, Ma.; Amerkhanova, Sh.K.; Uali, A. S. (Allerton Press, Inc., 2011)
A new process for the hydrogenation of coal in the presence of wide cut coal tar was proposed; it involves cavitation treatment, mixing with catalytic additives, and heating the resulting mixture at an elevated pressure in an atmosphere of hydrogen. The yields of hydrocarbon fractions to 300°C and gas condensate were evaluated.